An Evaluation of Food Wastes in Supplier-Retailer Interface: Evidences from UK and India. - Vasudev, Archita (2011)
Purpose – The aim of this thesis is to evaluate the causes of food waste in supplier-retailer interface. The objective is to identify good practices for suppliers and retailers so that food waste can be minimised.